2006
DOI: 10.1111/j.1346-8138.2006.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in patients with psoriasis

Abstract: Psoriasis can have a significant impact upon sexual function. The aim of this study was to investigate sexual function in females and males with psoriasis and to evaluate whether coexistent depression has an additional negative effect on sexual function in these patients. A total of 66 female subjects (39 with psoriasis and 27 healthy volunteers as a control group) and 70 male subjects (39 with psoriasis and 31 healthy volunteers as a control group) were enrolled in the study. A Psoriasis Area and Severity Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
83
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 22 publications
9
83
1
4
Order By: Relevance
“…3 Moreover, in the current study, women with AI reported age at disease onset approximately 6 years younger compared with male patients, which DLQI, mean 6 SD (range) 14.4 6 6.6 (1-26) 9.6 6 6.9 .03* FKKS SSEX, mean 6 SD (range) 19.5 6 5.1 (12-32) 23.5 6 5.8 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) .02* Sartorius score, mean 6 SD (range) 52.9 6 35.5 (7-138) 52. 8 6 27.3 (17-114) .72…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…3 Moreover, in the current study, women with AI reported age at disease onset approximately 6 years younger compared with male patients, which DLQI, mean 6 SD (range) 14.4 6 6.6 (1-26) 9.6 6 6.9 .03* FKKS SSEX, mean 6 SD (range) 19.5 6 5.1 (12-32) 23.5 6 5.8 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) .02* Sartorius score, mean 6 SD (range) 52.9 6 35.5 (7-138) 52. 8 6 27.3 (17-114) .72…”
Section: Discussionmentioning
confidence: 52%
“…Examples are psoriasis vulgaris, [16][17][18] atopic dermatitis, 13 chronic hand eczema, 19 vitiligo, and chronic urticaria. 20 To our knowledge, the degree of sexual dysfunction in patients with AI is unknown, until today.…”
mentioning
confidence: 99%
“…On the other hand, anxiety and depression, two of the main psychological comorbidities of psoriasis patients and also linked to ED, have seldom been assessed in these studies. Only one study has attempted to take into account the influence of depression on sexual function in people with psoriasis (Turel Ermertcan et al, 2006), although the authors did not concurrently assess anxiety, other physical comorbidities, or health habits. Thus, no study to date has considered the importance of anxiety in the relationship betweenpsoriasisandED (Table 1).Anxietyanddepressioncould be intermediatefactors betweenpsoriasisand ED,as they are more frequent among patient with psoriasis and are associated with ED.…”
Section: Introductionmentioning
confidence: 99%
“…clothes may stick to open areas and traumatize lesions),7 which can lead to further impairment in HRQOL. Psoriasis also impacts emotional and sexual functioning, which disrupts social interactions and intimate relationships 8, 9, 10, 11, 12, 13, 14. Sensitive issues, however, such as sexual relationships, typically are not assessed by clinicians 12.…”
Section: Introductionmentioning
confidence: 99%